Synthesis of carboxymethyl cellulose (CMC) from delignified Dyera Costulata / Rafidah Jalil, Mahanim Sarif ... [et al.] - Jalil, Rafidah; Sarif, Mahanim; Elham, Puad; Hashim, Shaharuddin (Universiti Teknologi MARA Shah Alam, 2022)
Carboxymethyl cellulose (CMC) was synthesised using Jelutong (Dyera costulata) plantation thinning biomass of 12 years old. The samples were delignified via pulping and bleaching process to remove lignin and hemicelluloses. The pulping process was carried out using 10% sodium hydroxide at various reaction times (1 - 5 hr) and temperatures (27 °C and 100 °C). The synthesis of CMC was carried out via alkalisation and etherification methods using sodium monochloroacetate. The sodium hydroxide concentration used during alkalisation varied from 30 to 50%. The highest yield of CMC obtained was 165%. The characterisation of CMC obtained includes its morphology structure, degree of substitution (DS), and reaction efficiency (RE). A higher DS value was obtained (0.723) for treated biomass (100 °C) with higher concentration of sodium hydroxide used (40%) during synthesis. The CMC DS value obtained from this experiment falls within the commercial CMC DS values reported.